Evaluation of Efficacy and Safety of Etanercept Therapy in Patients with Early and Late Juvenile Idiopathic Arthritis without Systemic Manifestations - T. M. Bzarova; E. I. Alexeeva; S. I. Valieva; R. V. Denisova; K. B. Isaeva; E. G. Chistyakova; A. M. Chomakhidze; T. V. Sleptsova; A. N. Fetisova; N. I. Taibulatov ("Paediatrician" Publishers LLC, 2015)
Background: An issue related to the terms of assignment of genetically engineered biological agents to patients with juvenile idiopathic arthritis (JIA) still remains debatable in pediatric rheumatology.Objective: Our aim was to evaluate the efficacy and safety of etanercept therapy in early and late JIA without systemic manifestations.Methods: An observational comparative study. The participants were divided into 2 groups. Patients of the treatment group (n = 98) - with early arthritis (lasting less than 2 years), and patients of the control group (n = 99) - with late arthritis (lasting more than 2 years). All children received etanercept in a dose of 0.4 mg/kg bodyweight 2 times per week subcutaneously. The efficacy of the therapy was evaluated for 3 years using the criteria of the American College of Rheumatology (ACRрedi), remission criteria by C. Wallace and JADAS71 index. Results: Total number of patients with JIA under the study is 197. After 6 months, the improvement according to the ACRpedi criteria 30/50/70 was recorded in 97/97/91% and 98/96/88%, and after 1 year - in 100/100/99% and 99/94/92% of patients with early and late arthritis, respectively. The efficacy of etanercept according to criteria by C. Wallace and JADAS71 index in early arthritis was higher than in late arthritis within 2 years of observation.Conclusion: Etanercept is more effective in early JIA than in late JIA without systemic manifestations.